Vpisovanje Njene zgodbe v ideološke konstrukte popularne kulture - Žikić, Biljana (Monitor ISH, 2005)
Her story in the ideological framework of popular culture. The article is based on a content and discourse analysis of 35 texts, submitted to the editorial office of the women's supplement Ona (She) for the open competition Njena zgodba - Rojstvo (Her Story - Birth). The analysis has revealed narrative structures, motifs, and themes matching the global picture of popular women's genres. The large consumption and reproduction of these genres is rooted in universal female fantasies, desires and problems regardless of national, generational, ethnic or class boundaries. At the same time, this women's (sub)culture is a channel through which their private issues are given a public voice.
Keywords: ženski žanri; woman; ženske; discourse; diskurz; popularna kultura; diskurzivna analiza; ženske revije